Дефекты производства и старение как основные факторы возможного ненормального действия артиллерийских боеприпасов - Анипко, О. Б.; Хайков, В. Л. (НТУ "ХПИ", 2011)
As a result of the spent literary review principal causes of abnormal action an ammunition (AAA) have been considered. In order to avoid possible AAA at shooting necessity of carrying out of 100 % rentgenotomografics the control of an ammunition not only at a production phase is proved, but also at their technical operation in an arsenal (base) and at the enterprises recycling an artillery ammunition.
Keywords: артиллерийские боеприпасы; артиллерийский выстрел; разрыв орудийного ствола; ненормальное действие боеприпаса; геронтологические изменения; взрывчатые вещества; старение пороха